2006
DOI: 10.1029/2005jd006967
|View full text |Cite
|
Sign up to set email alerts
|

Polar stratospheric ice cloud above Spitsbergen

Abstract: [1] Within the extremely cold and stable polar vortex of winter 2004-2005 a polar stratospheric ice cloud was observed from Ny-Å lesund (Spitsbergen) on 26 January 2005. The observation of a cloud with backscatter ratios up to 23 and volume depolarization larger than 50% is unique in our 15 year ground-based lidar data record. Simultaneous balloon-borne water vapor measurements indicate the presence of mesoscale ice clouds nearby. Normally, low horizontal wind speeds inside the inner vortex prevent vertical wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 64 publications
(78 reference statements)
2
26
1
Order By: Relevance
“…Satellite measurements by Atmospheric Chemistry Explorer (ACE) (Jin et al, 2006a) also indicated inhomogeneous denitrification in the vortex between mid-January and mid-March, between 400 K and 550 K. The area where the more rare ice PSC Type II could form, at even colder temperatures, was also among the largest in the observational record at 50 hPa, along with the winters 1995/96 and 1983/84. On 26 January, Type II PSCs were in fact observed for the first time in 15 years of observations above Spitzbergen (79 • N) (Maturilli and Dörnbrack, 2006). Associated with this, large-scale dehydration, where there is uptake of water out of the gas phase, presumably during ice cloud formation, was detected by EOS MLS over parts of the Arctic at 18-19 km at around the same time .…”
Section: Introductionmentioning
confidence: 80%
“…Satellite measurements by Atmospheric Chemistry Explorer (ACE) (Jin et al, 2006a) also indicated inhomogeneous denitrification in the vortex between mid-January and mid-March, between 400 K and 550 K. The area where the more rare ice PSC Type II could form, at even colder temperatures, was also among the largest in the observational record at 50 hPa, along with the winters 1995/96 and 1983/84. On 26 January, Type II PSCs were in fact observed for the first time in 15 years of observations above Spitzbergen (79 • N) (Maturilli and Dörnbrack, 2006). Associated with this, large-scale dehydration, where there is uptake of water out of the gas phase, presumably during ice cloud formation, was detected by EOS MLS over parts of the Arctic at 18-19 km at around the same time .…”
Section: Introductionmentioning
confidence: 80%
“…A complete and extended Arctic PSC climatology in Ny-Å lesund has been recently reported by Maturilli et al (2005) and Massoli et al (2006), where a comparison with the PSC lidar observations in the Antarctic McMurdo Station was also included. Different types of polar stratospheric clouds were historically first identified according to their optical parameters retrieved by lidar: the backscattering ratio R and the volume depolarization ratio d V Toon et al 1990).…”
Section: Arctic Psc Climatology In Ny-å Lesund Reported By Long-term mentioning
confidence: 99%
“…Over Ny-Å lesund, they have been detected only once, on 26 January 2005 (Maturilli and Dö rnbrack 2006), and were attributed to unusually strong mesoscale stratospheric temperature anomalies. The most important aspects characterizing PSC presence over Ny-Å lesund are summarized in Table 2, as extracted from Maturilli et al (2005) and Massoli et al (2006).…”
Section: Arctic Psc Climatology In Ny-å Lesund Reported By Long-term mentioning
confidence: 99%
See 1 more Smart Citation
“…In situ observations by research aircraft and dropsondes provided validation, at least of the general characteristics of the wave disturbances. Maturilli and Dörnbrack (2006), modelled waves over Svalbard (with 4 km horizontal resolution) and found waves with 10-20 km horizontal wavelength, and amplitude up to a few m/s in vertical wind. Only indirect validation of the model results was possible in terms of observation (by lidar) of polar stratospheric clouds composed of ice.…”
Section: Winter Storm Tracks Very Often Bring Deep Depressions Intomentioning
confidence: 99%